Physagulide Q suppresses proliferation and induces apoptosis in human hepatocellular carcinoma cells by regulating the ROS-JAK2/Src-STAT3 signaling pathway. Issue 21 (23rd February 2017) - Yang, Yan-Wei; Yang, Lei; Zhang, Chao; Gao, Cai-Yun; Ma, Ting; Kong, Ling-Yi
Abstract : Physagulide Q (PQ), a new natural compound, was isolated from Physalis angulata L. in our laboratory. Abstract : Physagulide Q (PQ), a new natural compound, was isolated from Physalis angulata L. in our laboratory. In this study, we observed that PQ suppressed cell proliferation and induced apoptosis in human hepatocellular carcinoma (HCC) cells. Signal transducer and activator of transcription 3 (STAT3) regulates the expression of various genes to control cell cycle progression and programmed cell death. PQ inhibited the phosphorylation of STAT3 on Tyr705 by suppressing the phosphorylation of its upstream protein kinases Janus-activated kinase 2 (JAK2) and Src. Furthermore, we found that PQ could induce production of reactive oxygen species (ROS) in human HCC cells. GSH, a ROS scavenger, abrogated the inhibitory effect of PQ on the JAK2/Src-STAT3 pathway in human HCC cells. These results suggested that PQ inhibited the STAT3 signaling pathway through the generation of ROS in human HCC cells.